Historical Imagination and the Unspoken Assumptions of Our Age. Issue 2 (4th March 2023) - Rhode, Benjamin
Abstract: This article discusses changing conceptions of how the study of history should best inform present challenges. It contrasts the 'historical sensibility' embodied by Michael Howard with the teleological 'historicism' decried by Karl Popper. It explores what Howard termed the historical 'imagination' – the recreation of the belief structures which made historical events and developments possible – and his argument of how the study of history, including the history of foreign countries, might cultivate cultural empathy. It also examines James Joll's concept of 'unspoken assumptions' and considers how it and Howard's ideas might illuminate our understanding of our own age.